Fostering Community-Based Solid Waste Management Through Participatory Action Research: Evidence from Rural Indonesia - Muhammad Abdul Halim Sidiq; Haidar Idris; Aminatuz Zahroh; Zainil Ghulam; Akhmad Afnan Fajarudin (Khidmatuna : Jurnal Pengabdian Masyarakat, 2025)
Rural solid waste management remains a persistent governance and public-health challenge in Indonesia, particularly in communities where disposal infrastructure is limited and open dumping has become normalised. This article examines how Participatory Action Research (PAR) fostered community-based solid waste management in Pandansari Hamlet, Tigasan Wetan Village, Probolinggo Regency. Using a qualitative-dominant design, the study integrated participatory observation, social mapping, focus group discussions, visual documentation, and community reflection conducted from December 2024 to January 2025. The PAR cycle comprised trust-building, problem diagnosis, deliberative planning, collective action, and reflective evaluation. The intervention identified three interrelated barriers: the transition from organic to mixed household waste, dependence on external infrastructure, and the normalisation of unsanitary disposal practices. By mobilising religious networks, neighbourhood leadership, and gotong royong, residents implemented clean-ups in three critical zones and established a small communal disposal facility. The findings show that PAR strengthened environmental awareness, enabled local consensus, and converted community concern into practical action. The article contributes to community-based waste-management literature by demonstrating that rural sustainability initiatives depend not only on technical facilities but also on the activation of social capital, locally legitimate leadership, and culturally embedded collective learning. The study recommends institutional follow-up through RT/RW rules, village-supported waste facilities, and circular-economy mechanisms such as waste banks linked to local governance.